Rancang Bangun Lab Komputer Virtual Berbasis Cloud Computing Menggunakan Openstack Pada Jaringan Terpusat - Nelmiawati Nelmiawati; Nur Cahyono Kushardianto; Ahmad Hamim Tohari; Yan Prada Hasibuan; Dwi Ely Kurniawan (Politeknik Negeri Batam, 2018)
Politeknik Negeri Batam is one college that gives higher priority to practicum activity. Students are therefore faced with a larger practical task than theory, making it more laboratory than practicum sessions. While access to the lab is quite limited. Virtual computer labs using Cloud Computing technology can be a solution to overcome this limitation. The author has been doing research on the design of Cloud Computing's virtual computer lab using OpenStack on a centralized network and has got some results. Tests are performed with specific server specifications and use the OpenStack platform. And the results of testing of the virtual computer lab with case studies of object-based programming courses show the server used during testing can run virtual computer lab with 9 computers well. While in the case study there are 30 computers per lab. This is due to hardware resources that are not good enough.